Literature review on the relationship between Artificial Intelligence Technologies with Digital Sports Marketing and Sports Management - Kemal Gökhan Nalbant; Sevgi Aydın (Universitas Majalengka, 2022)
In recent years, artificial intelligence has shown its supremacy in various domains in a wide range of amusement games and has increased its utilization in the sports industry. The computer vision program used for matches provides a complete analysis of the matches that have happened, gathers and categorizes the data so that the coach or teams may make better strategic planning decisions, and displays the study results. They can make assessments that individuals ordinarily cannot do because of applications of artificial intelligence. The players' performance on their teams may be evaluated in this manner, allowing coaches to devise optimal game-play techniques for their respective squads. Analysis performed using artificial intelligence is also applied in the sporting arena, namely in motorsports racing. Follow-up on fouls committed is accomplished with artificial intelligence, and a chance to get an advantage over one's rivals in terms of strategy is investigated and pursued. The advent of new digital technologies has brought about a revolution in sports marketing, as in every other industry. It has led to the development of digital sports marketing. In this study, an examination employing artificial intelligence and digital technology was carried out, with the primary emphasis on digital sports management and digital sports marketing studies. There has been an investigation into the potential for many technologies, including artificial intelligence, artificial neural networks, the metaverse, virtual reality, and augmented reality, to be used in competitive sports.